Use of a next generation maleimide in combination with THIOMAB™ antibody technology delivers a highly stable, potent and near homogeneous THIOMAB™ antibody-drug conjugate (TDC). Issue 40 (10th May 2017) - Nunes, João P. M.; Vassileva, Vessela; Robinson, Eifion; Morais, Maurício; Smith, Mark E. B.; Pedley, R. Barbara; Caddick, Stephen; Baker, James R.; Chudasama, Vijay
Abstract : Conjugation of next generation maleimides to engineered cysteines in a THIOMAB™ antibody delivers a highly stable and potent THIOMAB™ antibody-drug conjugate. Abstract : Herein we demonstrate that conjugation of a next generation maleimide (NGM) to engineered cysteines in a THIOMAB™ antibody delivers a THIOMAB™ antibody-drug conjugate (TDC) with a drug loading of ca. 2. This TDC is highly stable in blood serum conditions, selective and potent towards HER2 expressing cell lines and meets the current criteria for optimised antibody-drug conjugates (ADCs).